L’università e le disuguaglianze fra i giovani tra Ottocento e Novecento: le politiche per il diritto allo studio - Battilani, Patrizia; Menzani, Tito (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
The transformation of tertiary education from an experience reserved for a small elite to a tool for social mobility was one of the great challenges of the 20th century, when rising enrollment began to undermine the traditional elitist model. This essay aims to understand the impact of tuition fee exemptions and subsidies on opening up to new social classes, investigating the period from the Unification of Italy to the 1960s, essentially before the full establishment of mass university education. In order to contextualize the national picture in the concrete life of universities, we will examine the case of Bologna, thanks to materials preserved in university archives and the archives of institutions (Opera universitaria and Er.Go) that supported low-income students.